2011
DOI: 10.1007/s10566-011-9142-x
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Attendance Rates and Quality of Teacher-Child Interactions in At-Risk Preschool Classrooms: Contribution to Children’s Expressive Language Growth

Abstract: The present research examines whether children's daily attendance rates would be predictive of gains in expressive language within the context of high-quality preschool classrooms. The quality of preschool classrooms was assessed by measuring the quality of the teacher's interactions with the children in his or her classroom. Hierarchical linear models, nesting children within classroom, were used to examine children's growth in expressive language in two independent samples (n = 129 children in 14 classrooms;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 45 publications
2
20
0
2
Order By: Relevance
“…Nineteen studies [34,36,38,42,45,46,4951,5355,57,59–61,64,65,67] used the most recent version of the CLASS [72], 5 studies [43,48,52,62,63] used an earlier version [73], which did not include the Language Modeling dimension, and 11 studies [7,8,30,31,3941,44,47,56,58] used CLASS domains (emotional and/or instructional climate) from the earlier version. Since we did not have data on the comparability of scores when these scales were combined vs. analyzed separately we chose the conservative route and tested the Emotional Climate domain separately.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nineteen studies [34,36,38,42,45,46,4951,5355,57,59–61,64,65,67] used the most recent version of the CLASS [72], 5 studies [43,48,52,62,63] used an earlier version [73], which did not include the Language Modeling dimension, and 11 studies [7,8,30,31,3941,44,47,56,58] used CLASS domains (emotional and/or instructional climate) from the earlier version. Since we did not have data on the comparability of scores when these scales were combined vs. analyzed separately we chose the conservative route and tested the Emotional Climate domain separately.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 35 eligible articles, 29 studies [7,8,30,31,34,36,3845,47,48,50,51,53,54,56,58,60–65,67] provided data for at least one outcome variable that was also included in at least two other samples. Six studies [46,49,52,55,57,59] are not included in Figs 2–7 because they report only outcomes found in less than three samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In early childhood settings in the United States, children's attendance can be highly variable; for instance, one study of Head Start participants reported a mean daily attendance rate of 85% (Hubbs-Tait et al, 2002). Importantly, attendance rates, even when controlling for key background factors, are associated with children's growth in social skills (Hubbs-Tait et al, 2002) and language skills (Logan, Piasta, Justice, Schatschneider, & Petrill, 2011). In the present study, we cannot disentangle the effects of regular attendance in childcare from SPELL exposure, and it may be possible that the two interact in important ways.…”
Section: Discussionmentioning
confidence: 99%